2016
DOI: 10.5604/17331331.1215611
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Identification of Endophytic Streptomyces Species from Schima wallichii as Potential Biocontrol Agents against Fungal Plant Pathogens

Abstract: A b s t r a c tThe prospective of endophytic microorganisms allied with medicinal plants is disproportionally large compared to those in other biomes. The use of antagonistic microorganisms to control devastating fungal pathogens is an attractive and eco-friendly substitute for chemical pesticides. Many species of actinomycetes, especially the genus Streptomyces, are well known as biocontrol agents. We investigated the culturable community composition and biological control ability of endophytic Streptomyces s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Members of this phylum are well known for their ability to produce secondary metabolites with application in the agricultural, pharmaceutical and medical industries ( Himaman et al, 2016 ). Several studies proposed their use as BCAs ( El-Tarabily et al, 2000 ; Kunoh, 2002 ; Cao et al, 2005 ; Prapagdee et al, 2008 ; Mingma et al, 2014 ). They play key roles as plant growth promoters, disease resistance inducers and drought tolerance stimulators ( Himaman et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Members of this phylum are well known for their ability to produce secondary metabolites with application in the agricultural, pharmaceutical and medical industries ( Himaman et al, 2016 ). Several studies proposed their use as BCAs ( El-Tarabily et al, 2000 ; Kunoh, 2002 ; Cao et al, 2005 ; Prapagdee et al, 2008 ; Mingma et al, 2014 ). They play key roles as plant growth promoters, disease resistance inducers and drought tolerance stimulators ( Himaman et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among the 56 endophytic bacteria obtained from P. ostii, Bacillus was the most dominant genus (55.4% of all isolates); this finding is consistent with previous reports on different hosts (El-Deeb et al 2013). In addition to Bacillus sp., other genera, such as Streptomyces from Schima wallichi (Passari et al 2016) and Leifsonia from ginseng roots, have also been reported in medicinal plants (Qiu et al 2007). Endophytic Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…4). Both Streptomyces and Pseudomonas are prolific producers of bioactive compounds, including various antibiotics, antitumor, and plant growth hormones (Wu et al 2011;Passari et al 2016). Therefore, these NRPS genes may be capable of producing unique bioactive compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they operate as hosts for several endophytes, which are known to produce a variety of bioactive substances [ 25 – 27 ]. Endophytic microorganisms showed a wide range of biological activity, including anticancer, antibacterial, antifungal, immunomodulatory, antioxidant, and textile dyeing activities [ 28 30 ]. Endophytic fungi are a significant part of the plant microbiota that is present throughout the plant tissues without harming the host.…”
Section: Introductionmentioning
confidence: 99%